Comportamentos de movimento e indicadores de obesidade: um estudo em pré-escolares que atendem ou não as recomendações de sono - Souza, Alesandra Araújo de (2022)
BACKGROUND: in the last century, children of different age groups have slept about 0.75 minutes less per year. In preschool children, it is observed that there is a daily sleep deficit of half an hour, which can imply short sleep durations both in this and later in life. As a preventive strategy, sleep hygiene habits such as not being exposed to screens before going to bed, staying physically active, and the low accumulation of time in sedentary behavior (SB) are daily recommendations for adequate sleep duration in this age group. However, the literature reports controversial results, as preschoolers considered physically active are also those who sleep less than the recommended. At the same time, the relationship between sleep and SB, and more specifically with screen time (ST), is not established. Thus, the relationship between physical activity (PA) and SB of preschoolers who sleep or not the recommended is unknown. In addition, although adolescents and adults with short sleep duration have higher body mass index (BMI), this relationship in preschoolers, and whether preschoolers who get adequate sleep or not have differences or associations with obesity indicators are also unclear. AIM: To analyze the possible associations between PA, SB, ST, and body composition indicators of preschoolers who meet or do not meet the sleep recommendations. METHODS: cross-sectional, observational study with data from the project: Movement's Cool. A total of 272 preschoolers (138 girls; 4.5±0.8 years) participated in the project. Parents reported sleep duration (SD) on weekdays and weekends through an interview. Preschoolers were categorized as 1) meet the recommendations; 2) do not meet the recommendations. The accumulated time in AF and SB was determined using accelerometry (wGT3x-BT, Actigraph). The parents reported the ST (smartphone, notebook, computer, and television) through an interview. To analyze the composition of 24-hour movements, Compositional Analysis was used; to determine the 24-hour movement behavior patterns and the relationship with obesity indicators, Latent Profile Analysis and Linear Regression were used; to know the direct and indirect paths between the 24-hour behaviors with the BMI z-score (BMIz), Path Network Analysis was used. RESULTS: preschoolers who do not meet the sleep recommendations present a composition of movements with a more significant accumulation of SC (+32 minutes/day) and light PA (LPA) (+24 minutes/day), and this evidence is considered moderate and strong, respectively. In addition, preschoolers who do not meet sleep recommendations and accumulate less than 60 minutes of moderate to vigorous PA (MVPA) have a positive relationship with BMI, while those who do have a negative relationship. The non-linear analysis showed a negative relationship between sleep-BMIz (three years) and a positive one (four and five years). CONCLUSION: preschoolers who meet sleep recommendations engage in PA for longer, have sleep as a protective factor for BMI when they do not accumulate adequate time in MVPA and, according to age, the relationship of sleep with PA, ST, and sleep varies.